Kerugian Keuangan Negara dalam Undang-Undang Pemberantasan Tindak Pidana Korupsi Perspektif Yuridis Normatif - Permata Bela Pertiwi; Muhammad Reyhan Daru Quthni (Rechtenstudent, 2023)
Handling corruption cases will be less than optimal when state financial losses cannot be recovered. Recovery of state losses is of course necessary to implement development programs that have not been implemented. Handling existing corruption cases, including compensation for state losses, is one of the efforts of law enforcement officials to handle cases of criminal acts of corruption. The main problem of this study is how to apply the calculation of state financial losses before the Constitutional Court decision Number 25/PUU-XIV/2016 and how to apply the calculation of state financial losses afterward. Court No.25/PUU-XIV. 2016. This type of research is included in the legal research category. Although seen from its nature, this research is descriptive analysis. The application of the method for calculating state financial losses in Articles 2 (1) and 3 of Law Number 20 of 2001 amending Law Number 31 of 1999 concerning the Eradication of Corruption Crimes has undergone legal changes. The view regarding the application of state losses because there is no actual or potential state financial loss (potential loss) has changed the view regarding actual state losses (actual loss). After this decision removed phrases that could harm the state, making corruption a material crime, namely a factor that makes state losses absolutely impossible to prove.